2007
DOI: 10.1001/jama.297.4.387
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Subsequent Fracture After Low-Trauma Fracture in Men and Women

Abstract: ContextThere are few published long-term data on absolute risk of subsequent fracture (refracture) following initial low-trauma fracture in women and fewer in men.Objective To examine long-term risk of subsequent fracture following initial osteoporotic fracture in men and women.Design, Setting, and Participants Prospective cohort study (Dubbo Osteoporosis Epidemiology Study) in Australia of 2245 community-dwelling women and 1760 men aged 60 years or older followed up for 16 years from July 1989 through April 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
432
2
26

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 595 publications
(491 citation statements)
references
References 30 publications
31
432
2
26
Order By: Relevance
“…(6)(7)(8) In a study of 451 female in-patients aged 60 to 99 years with a fracture of the spine, olecranon, knee, or ankle, Lauritzen and colleagues compared the risk of a subsequent hip fracture with the age-specific incidence of hip fracture of the background population and found that the relative risk was 2.8 (95% CI 1.9-4.1) within 3 years of the primary fracture, and the increased risk then leveled off after 3 years. (8) In another study of 28,869 inpatients, a vertebral fracture was associated with a marked increase in subsequent incidence of hip and all fractures within the first year following the primary vertebral fracture in both men and women; the incidence then declined toward, but did not attain, baseline risk.…”
Section: Risk Of Subsequent Fractures In Older Peoplementioning
confidence: 99%
See 4 more Smart Citations
“…(6)(7)(8) In a study of 451 female in-patients aged 60 to 99 years with a fracture of the spine, olecranon, knee, or ankle, Lauritzen and colleagues compared the risk of a subsequent hip fracture with the age-specific incidence of hip fracture of the background population and found that the relative risk was 2.8 (95% CI 1.9-4.1) within 3 years of the primary fracture, and the increased risk then leveled off after 3 years. (8) In another study of 28,869 inpatients, a vertebral fracture was associated with a marked increase in subsequent incidence of hip and all fractures within the first year following the primary vertebral fracture in both men and women; the incidence then declined toward, but did not attain, baseline risk.…”
Section: Risk Of Subsequent Fractures In Older Peoplementioning
confidence: 99%
“…Also, in a prospective cohort study of 2245 communitydwelling women and 1760 men aged 60 years (including 905 women and 337 men with a low-trauma fracture such as of the upper limb, vertebra, hip, lower limb, rib, or ankle) living in Australia (Dubbo Osteoporosis Epidemiology Study), (6) 253 women and 71 men suffered a subsequent fracture during a mean follow-up of 4.3 years, giving a refracture rate of 6.2% (95% CI 5.5-7.0) and 5.7% (95% CI 4.5-7.2) per person-year in women and men, respectively. Relative risk (RR) of subsequent fracture was 1.95 (95% CI 1.70-2.25) in women and 3.47 (95% CI 2.68-4.48) in men, and all fracture locations apart from rib (men) and ankle (women) resulted in increased subsequent fracture risk, with the highest RRs following hip (RR ¼ 9.97, 95% CI 1.38-71.98) and clinical vertebral (RR ¼ 15.12, 95% CI 6.06-37.69) fractures in younger men.…”
Section: Risk Of Subsequent Fractures In Older Peoplementioning
confidence: 99%
See 3 more Smart Citations